Crosslinked type marine biodegradable polymer compound composed of different anionic polymer compounds and method for producing the same

A crosslinked marine biodegradable polymer compound, composed of specific anionic polymer compounds and a metal cation, addresses the challenge of biodegradability in marine environments by enhancing thermal and mechanical properties and promoting efficient biodegradation of resins in seawater.

JP2025052844APending Publication Date: 2025-04-07NISSHINBO IND INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023161795
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-07

AI Technical Summary

Technical Problem

Existing biodegradable resins face challenges in degrading efficiently in marine environments with low microorganism concentrations, and starch-based resins lose biodegradability when mixed with non-biodegradable polyester-based resins.

Method used

A crosslinked marine biodegradable polymer compound is developed, comprising anionic polymer compounds A and B with specific monovalent anionic groups and a metal cation, which enhances thermal and mechanical properties while promoting biodegradability in seawater.

Benefits of technology

The polymer compound exhibits high biodegradability in seawater, accelerating the decomposition of difficult-to-degrade resins and reducing environmental impact, while maintaining excellent thermal and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025052844000001
    Figure 2025052844000001
  • Figure 2025052844000002
    Figure 2025052844000002
  • Figure 2025052844000003
    Figure 2025052844000003
Patent Text Reader

Abstract

To provide a polymer compound which is excellent in thermal / machine physical properties and causes biodegradability in marine, and a marine biodegradable resin composition using the same.SOLUTION: There is provided a marine biodegradable polymer compound in which an anionic polymer compound A that has a linear or branched main chain, has two or more monovalent anionic groups at a terminal of the main chain, and has no ionic group at the side chain, and an anionic polymer compound B having two or more monovalent anionic groups at a side chain of a repeating unit are bonded through a di- or more-valent metal cation.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a crosslinked marine biodegradable polymer compound comprising different anionic polymer compounds and a method for producing the same. [Background technology]

[0002] In recent years, environmental pollution (marine pollution) and adverse effects on ecosystems caused by microplastics have become a problem, and various efforts have been launched to reduce the environmental burden. Among these, the development and popularization of biodegradable resins has been attracting attention.

[0003] On the other hand, although general biodegradable resins show high biodegradability in environments such as soil and sludge where there are many microorganisms responsible for decomposition, they have the disadvantage of being difficult to decompose in environments with extremely low microbial concentrations, such as in the ocean (Non-Patent Document 1).In addition, it has been found that the decomposition rate of resins that have been reported to be biodegradable in the ocean, such as polycaprolactone (PCL) and polyhydroxyalkanoic acid (PHA), varies greatly depending on the type of seawater, and it has been reported that this is influenced by various factors, such as the presence or absence of decomposing bacteria in the seawater, the number of bacteria, salt concentration, pH, water temperature, dissolved oxygen concentration, and amount of dissolved organic carbon (Non-Patent Document 2).

[0004] Although starch-based resins have been put to practical use and are on the market as biodegradable resins, most of them are mixed with polyester-based resins such as polybutylene adipate / terephthalate (PBAT) and polylactic acid (PLA), which are difficult to biodegrade in the ocean, because the physical properties of starch alone are significantly inferior. Therefore, even starch-based resins tend to have significantly reduced biodegradability in the ocean.

[0005] Under these circumstances, there is a demand for the development of materials that can be decomposed reliably in any type of seawater while maintaining their physical properties, as well as materials that can promote the decomposition of resins that are difficult to biodegrade in seawater and that also reduce the environmental impact. [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] Hideshige Takada, "Current Status of Microplastic Pollution, International Trends and Countermeasures," Journal of Japan Society for Material Cycle Management, Vol. 29, No. 4, pp. 261-269, 2018 [Non-Patent Document 2] Akira Ebisui and 4 others, "Decomposition of biodegradable plastics in seawater," Fisheries Engineering, Vol. 40, No. 2, pp. 143-149, 2003 Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a polymer compound that has excellent thermal and mechanical properties and can induce biodegradability in the ocean, and a marine biodegradable resin composition using the same. [Means for solving the problem]

[0008] As a result of intensive research aimed at solving the above-mentioned problems, the inventors have found that a polymer compound in which an anionic polymer compound A having a linear or branched main chain, a total of two or more monovalent anionic groups at the ends of the main chain and no ionic groups in the side chain, and an anionic polymer compound B having monovalent anionic groups in the side chains of two or more repeating units are bonded via a divalent or higher metal cation, exhibits excellent thermal and mechanical properties and high marine biodegradability.

[0009] Furthermore, the inventors discovered that by using this material in combination with a resin, particularly a biodegradable resin, the material undergoes primary decomposition in seawater first, and that (1) pores are formed in the resin material, increasing the specific surface area of ​​the resin and promoting the growth of microorganisms responsible for decomposition, and (2) the primary decomposition has the effect of promoting secondary decomposition, i.e., biodegradation by microorganisms, thereby ultimately promoting the biodegradation of resin materials in the ocean, thereby completing the present invention.

[0010] That is, the present invention provides the following marine biodegradable polymer compound and a method for producing the same. 1. A marine biodegradable polymer compound in which an anionic polymer compound A has a linear or branched main chain, a total of two or more monovalent anionic groups at the ends of the main chain, and no ionic groups in the side chains, and an anionic polymer compound B has monovalent anionic groups in the side chains of two or more repeating units, bonded via a divalent or higher metal cation. 2. The polymer compound of 1, wherein the mass ratio of the anionic polymer compound A to the anionic polymer compound B is 99:1 to 10:90. 3. The polymer compound of 1 or 2, wherein the main chain of the anionic polymer compound A is linear. 4. The polymer compound according to any one of 1 to 3, wherein the anionic polymer compound B contains a repeating unit having no ionic group. 5. The anionic polymer compound B is any one of the polymer compounds 1 to 4, wherein the main chain has an aliphatic unsaturated carbon-carbon bond. 6. The polymer compound according to any one of 1 to 5, wherein the monovalent anionic group of the anionic polymer compound A is a carboxylate anion. 7. The polymer compound according to any one of 1 to 6, wherein the monovalent anionic group of the anionic polymer compound B is a carboxylate anion or a sulfonate anion. 8. A polymer compound according to any one of 1 to 7, in which the monovalent anionic group of the anionic polymer compound B is bonded to a ring. 9. Any of the polymer compounds according to 1 to 8, wherein the anionic polymer compound A has a number average molecular weight of 500 to 10,000, and the anionic polymer compound B has a number average molecular weight of 500 to 10,000. 10. Any of the polymer compounds according to 1 to 9, wherein the anionic polymer compound A is a polymer in which repeating units are bonded together through at least one bond selected from an ester bond, an amide bond, an ether bond, and a urethane bond, and the anionic polymer compound B is a polymer in which repeating units are bonded together through at least one bond selected from an ester bond, an amide bond, an ether bond, and a urethane bond. 11. A polymer compound according to any one of 1 to 10, wherein the value obtained by dividing the number average molecular weight of the anionic polymer compound B by the average number of monovalent anionic groups in one molecule is 100 to 5,000. 12. The content of the divalent or higher metal cation is 1 to 300 eq / 10 5 The polymer compound according to any one of 1 to 11, wherein g is 13. The polymer compound according to any one of 1 to 12, wherein the divalent or higher metal cation is a calcium ion, a magnesium ion or an aluminum ion. 14. A marine biodegradation promoter comprising any one of the marine biodegradable polymer compounds of 1 to 13. A marine biodegradable resin composition comprising the marine biodegradation promoter of 15.14 and a resin. 16. The marine biodegradable resin composition of 15, wherein the resin is a biodegradable resin. 17. The marine biodegradable resin composition according to 15 or 16, wherein the content of the marine biodegradation promoter is 1 to 50 mass % and the content of the resin is 50 to 99 mass %. 18. A molded article obtained from the marine biodegradable resin composition according to any one of 15 to 17. 19. A method for producing a marine biodegradable polymer compound, comprising a step of crosslinking an anionic polymer compound A having a linear or branched main chain, a total of two or more monovalent anionic groups at the ends of the main chain, and no ionic groups in its side chain, and an anionic polymer compound B having monovalent anionic groups in the side chains of at least two repeating units, with a divalent or higher metal cation. Effect of the Invention

[0011] The marine biodegradable polymer compound of the present invention is a crosslinked product of an anionic polymer compound having a monovalent anionic group at the end and an anionic polymer compound having a monovalent anionic group in the side chain of the repeating unit via a metal cation, and therefore can achieve both thermal and mechanical properties and marine biodegradability. In addition, the marine biodegradable polymer compound gradually dissolves in seawater when it comes into contact with seawater, or exhibits hydrophilicity, so that a resin composition or molded article containing the same is accelerated in the ocean and is useful for marine pollution countermeasures. Since the marine biodegradable polymer compound has marine biodegradability, a composition or molded article containing the same is accelerated in the ocean and is useful for marine pollution countermeasures. By using a marine biodegradation promoter consisting of the marine biodegradable polymer compound of the present invention, an environmentally friendly composition or molded article can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] [Marine biodegradable polymer compounds] The marine biodegradable polymer compound of the present invention has a linear or branched main chain, has a total of two or more monovalent anionic groups at the ends of the main chain, and is formed by bonding an anionic polymer compound A having no ionic groups in the side chain and an anionic polymer compound B having monovalent anionic groups in the side chains of two or more repeating units via a divalent or higher metal cation. In the present invention, the term "main chain" refers to a molecular chain that forms the backbone of the polymer structure. The main chain may have a ring structure therein. The term "side chain" refers to a substituent bonded to the main chain.

[0013] In the marine biodegradable polymer compound of the present invention, the mass ratio of anionic polymer compound A to anionic polymer compound B is preferably A:B=99:1 to 10:90, more preferably 95:15 to 15:85, and even more preferably 90:10 to 20:80. When the mass ratio of anionic polymer compound A to anionic polymer compound B is within the above range, the flexibility derived from anionic polymer compound A and the thermal and mechanical properties derived from anionic polymer compound B can be compatible, and the polymer compound has good biodegradability.

[0014] The anionic polymer compound A may be linear or branched. From the viewpoint of the thermal and mechanical properties of the polymer compound after crosslinking, the anionic polymer compound A is preferably linear or branched and has a total of 2 to 10 monovalent anionic groups at the terminals of the main chain, more preferably has a total of 2 to 4 monovalent anionic groups at the terminals of the main chain, and further preferably has a linear polymer compound A and has a total of 2 monovalent anionic groups at the terminals of the main chain.

[0015] The anionic polymer compound B may contain a repeating unit having no ionic group in addition to the repeating unit having a monovalent anionic group, so long as it has a monovalent anionic group in two or more repeating units. In this case, the anionic polymer compound B is not particularly limited in the arrangement of its monomers, and may be any of a random copolymer, an alternating copolymer, a block copolymer, etc. In addition, the anionic polymer compound B may be linear or branched, but is preferably linear from the viewpoint of the thermal and mechanical properties of the polymer compound after crosslinking.

[0016] The anionic polymer compound B may have an aliphatic unsaturated carbon-carbon bond in the main chain. In this case, the number of aliphatic unsaturated carbon-carbon bonds per molecule is preferably 0.1 to 50 on average, more preferably 0.5 to 25, and even more preferably 1 to 10, so that strength and biodegradability can be compatible.

[0017] From the viewpoints of physical properties and safety, the monovalent anionic group contained in the anionic polymer compound A is preferably a carboxylate anion, a sulfonate anion or a phosphate anion, more preferably a carboxylate anion or a sulfonate anion, and even more preferably a carboxylate anion. The monovalent anionic groups contained in the anionic polymer compound A may be the same as or different from each other.

[0018] From the viewpoint of physical properties and safety, the monovalent anionic group contained in the anionic polymer compound B is preferably a carboxylate anion, a sulfonate anion or a phosphate anion, more preferably a carboxylate anion or a sulfonate anion, and even more preferably a sulfonate anion. The monovalent anionic groups contained in the anionic polymer compound B may be the same as or different from each other.

[0019] The monovalent anionic group contained in the anionic polymer compound B may be directly bonded to the main chain or may be bonded via a linking group, but considering the thermal and mechanical properties, it is preferable that it is directly bonded to the main chain or bonded via a linking group having 1 to 25 atoms, and more preferably that it is directly bonded to the main chain. When the monovalent anionic group is directly bonded to the main chain, it is more preferable that the main chain contains a ring and the monovalent anionic group is bonded to the ring. The ring may be an alicyclic ring or an aromatic ring, but is preferably an aromatic ring. In addition, the ring may be composed of only carbon atoms or may be a heterocyclic ring containing other atoms, but is preferably composed of only carbon atoms. When the monovalent anionic group is bonded to the main chain via a linking group, the structure of the linking group may be any of linear, branched, and cyclic, but is preferably linear or branched, and more preferably linear. The atoms constituting the linking group are not particularly limited, but are preferably carbon, oxygen, nitrogen, boron, sulfur, phosphorus, or silicon, and more preferably carbon, oxygen, nitrogen, or sulfur.

[0020] The molecular weight of the anionic polymer compound A is not particularly limited, but from the viewpoints of thermal and mechanical properties and biodegradability, the number average molecular weight is preferably 200 to 100,000, more preferably 300 to 50,000, and even more preferably 500 to 10,000.

[0021] The molecular weight of the anionic polymer compound B is not particularly limited, but from the viewpoints of thermal and mechanical properties and biodegradability, the number average molecular weight is preferably 200 to 100,000, more preferably 300 to 50,000, and even more preferably 500 to 10,000.

[0022] From the viewpoint of thermal and mechanical properties of the polymer compound after crosslinking, the value obtained by dividing the number average molecular weight of the anionic polymer compound B by the average number of monovalent anionic groups in one molecule is preferably 100 to 5000, more preferably 200 to 3000, and even more preferably 300 to 1000. Two or more monovalent anionic groups may be contained in one repeating unit, and one or more types of repeating units having a monovalent anionic group and repeating units not having a monovalent anionic group may be contained.

[0023] It is possible to further improve the thermal and mechanical properties by the combination of the anionic polymer compound A and the anionic polymer compound B. Specifically, the sum of the weighted average according to the mass ratio of the number average molecular weight of the anionic polymer compound A component contained in the marine biodegradable polymer compound and the weighted average according to the mass ratio of the number average molecular weight of the anionic polymer compound B component is preferably 500 to 50,000, more preferably 1,000 to 30,000, further preferably 1,500 to 10,000, and most preferably 2,000 to 8,000.

[0024] In this case, the anionic polymer compound A and the anionic polymer compound B are preferably combined by combining an anionic polymer compound A having a number average molecular weight of 200 to 20,000 with an anionic polymer compound B having a number average molecular weight of 300 to 30,000, more preferably by combining an anionic polymer compound A having a number average molecular weight of 500 to 10,000 with an anionic polymer compound B having a number average molecular weight of 500 to 20,000, and even more preferably by combining an anionic polymer compound A having a number average molecular weight of 500 to 3,000 with an anionic polymer compound B having a number average molecular weight of 1,500 to 5,000.

[0025] From the viewpoints of thermo-mechanical properties and biodegradability, the anionic polymer compound A is preferably one in which repeating units are bonded by at least one bond selected from ester bonds, amide bonds, ether bonds and urethane bonds, more preferably one in which repeating units are bonded by ester bonds or amide bonds, and even more preferably one in which repeating units are bonded by ester bonds. Moreover, from the viewpoints of thermo-mechanical properties and biodegradability, the repeating units are preferably aliphatic or aromatic having 1 to 20 carbon atoms or a combination thereof, more preferably aliphatic or aromatic having 1 to 10 carbon atoms or a combination thereof, and even more preferably aliphatic having 1 to 10 carbon atoms.

[0026] From the viewpoints of thermo-mechanical properties and biodegradability, the anionic polymer compound B is preferably one in which repeating units are bonded by at least one bond selected from ester bonds, amide bonds, ether bonds and urethane bonds, more preferably one in which repeating units are bonded by ester bonds or amide bonds, and even more preferably one in which repeating units are bonded by ester bonds. Moreover, from the viewpoints of thermo-mechanical properties and biodegradability, the repeating units are preferably aliphatic or aromatic having 1 to 20 carbon atoms or a combination thereof, more preferably aliphatic or aromatic having 1 to 10 carbon atoms or a combination thereof, and even more preferably a combination of aliphatic and aromatic having 1 to 10 carbon atoms.

[0027] The anionic polymer compound A has a relative cellulose biodegradability of preferably 40% or more, more preferably 50% or more, even more preferably 60% or more, and most preferably 80% or more. In the present invention, the relative cellulose biodegradability is the maximum decomposition degree relative to the maximum cellulose decomposition degree within two years after immersion in seawater. The relative cellulose biodegradability can be measured by ASTM D6691, known marine biodegradation test methods, etc., or BOD modified with reference to them.

[0028] The anionic polymer compound B preferably has a relative cellulose biodegradability of 40% or more, more preferably 50% or more, further preferably 60% or more, and most preferably 80% or more.

[0029] The anionic polymer compound A preferably has a softening point or melting point. The anionic polymer compound A is preferably solid or liquid at room temperature, and specifically, the lower limit of the softening point or melting point is preferably -80°C or higher, -40°C or higher, 0°C or higher, 40°C or higher, and 80°C or higher, in that order, and the upper limit is preferably 180°C or lower, 150°C or lower, and 120°C or lower, in that order. In consideration of handling, it is preferable that the softening point or melting point is preferably within the range of -80 to 180°C, more preferably -40 to 120°C.

[0030] The anionic polymer compound B preferably has a softening point or melting point. The anionic polymer compound B is preferably solid or liquid at room temperature, and specifically, the lower limit of the softening point or melting point is preferably 0°C or more, 25°C or more, 40°C or more, 80°C or more, and 100°C or more, in that order, and the upper limit is preferably 180°C or less, 150°C or less, and 120°C or less, in that order. In consideration of handling, it is preferable that the softening point or melting point is preferably within the range of 0 to 180°C, more preferably 25 to 120°C.

[0031] The anionic polymer compound A is preferably dissolved in water or a water-miscible solvent, more specifically, it is preferably dissolved in water or a water-miscible solvent at a concentration of 1 mass %, 5 mass %, 10 mass %, 20 mass %, 30 mass %, 50 mass % or more, respectively. The water or water-miscible solvent may be cooled or heated.

[0032] The anionic polymer compound B is preferably dissolved in water or a water-miscible solvent, more specifically, it is preferably dissolved in water or a water-miscible solvent at a concentration of 1 mass %, 5 mass %, 10 mass %, 20 mass %, 30 mass %, 50 mass % or more, respectively. The water or water-miscible solvent may be cooled or heated.

[0033] Examples of solvents that are miscible with water include lower alcohol solvents such as methanol, ethanol, 1-propanol, and 2-propanol, and amphipathic solvents such as acetone, acetonitrile, tetrahydrofuran (THF), dimethylformamide (DMF), dimethylsulfoxide (DMSO), and N-methylpyrrolidone (NMP). From the viewpoints of miscibility with water, solubility, and ease of handling, ethanol, acetonitrile, THF, and NMP are preferred, and ethanol and acetonitrile are more preferred.

[0034] The method for producing the anionic polymer compound A is not particularly limited, but for example, the anionic polymer compound A can be produced by introducing the monovalent anionic group via a linking group into a compound (hereinafter also referred to as polymer compound A) having a linear or branched main chain, a total of two or more active functional groups such as hydroxyl groups, amino groups, thiol groups, etc. at the terminals of the main chain, and no ionic groups at the side chains.

[0035] Commercially available or synthesized products can be used as the polymer compound A. Commercially available products include, for example, Kuraray Polyol P-1010, P-2010, P-2020, P-2050, P-520, C-590, and F-1010 (Kuraray Co., Ltd.), Plaxel 210B, 220N, and 308 (Daicel Co., Ltd.), polypropylene glycol, diol type 1000, polypropylene glycol, triol type 300 (FUJIFILM Wako Pure Chemical Industries, Ltd.), poly(propylene glycol) bis(2-aminopropyl ether) 400, and poly(propylene glycol) bis(2-aminopropyl ether) 2000 (Sigma-Aldrich Japan LLC). When synthesizing the polymer compound A, for example, two or more suitable raw materials are selected from divalent or higher carboxylic acids, divalent or higher alcohols, divalent or higher amines, divalent or higher isocyanates, etc., and the polymer compound A can be obtained by polycondensation or polyaddition reaction. For example, polyester polyol can be obtained by polycondensation of divalent or higher carboxylic acids and divalent or higher alcohols, polyamide polyamine can be obtained by polycondensation of divalent or higher carboxylic acids and divalent or higher amines, and polyurethane polyol can be obtained by polyaddition of divalent or higher isocyanates and divalent or higher alcohols. However, the combination is not limited to this, and three or more raw materials having different functional groups may be used, or two or more different raw materials having the same functional group may be used simultaneously. In addition, when a trivalent or higher raw material is used, the total amount of the trivalent or higher raw materials is preferably 0.01 to 50 mol%, more preferably 0.05 to 30 mol%, and most preferably 0.1 to 15 mol% of the total amount of the raw materials. In this case, in order to facilitate the reaction, a derivative of each raw material may be used instead of the raw material. In the reaction, a base catalyst such as DBU or triethylamine, or a metal catalyst such as dibutyltin dilaurate or titanium tetraisopropoxide may be used.

[0036] Examples of the divalent or higher carboxylic acid include oxalic acid, malonic acid, fumaric acid, maleic acid, succinic acid, adipic acid, sebacic acid, 1,2,3-propanetricarboxylic acid, aconitic acid, malic acid, citric acid, phthalic acid, isophthalic acid, terephthalic acid, 1,3,5-benzenetricarboxylic acid, 2,6-naphthalenedicarboxylic acid, biphenyldicarboxylic acid, trimellitic acid, and pyromellitic acid.

[0037] Examples of the dihydric or higher alcohol include ethylene glycol, glycerol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 2-butene-1,4-diol, 1,2,3-butanetriol, 1,2,4-butanetriol, 1,5-pentanediol, 2,4-pentanediol, 1,2,5-pentanetriol, 2-hydroxy-2-ethyl-1,3-propanol, pentaerythritol, 1,2-cyclohexanediol, 1,3-cyclohexanediol, 1,4-cyclohexanediol, 1,3,5-cyclohexanetriol, 1,6-hexanediol, 2,5-hexanediol, 3-methyl Examples of the hydroxypropyl ether include 1,5-pentanediol, 1,7-heptanediol, 1,4-benzenedimethanol, 3,6-diazaoctane-1,8-diol, 2,6-dihydroxynaphthalene, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,16-hexadecanediol, 1,18-octadecanediol, phloroglucinol, pyrogallol, 1,2,4-benzenetriol, 4,4'-dihydroxybiphenyl, 4,4'-dihydroxydiphenylmethane, 4,4'-dihydroxydiphenyl ether, and polyethylene glycol.

[0038] Examples of the divalent or higher amines include ethylenediamine, 1,2-diaminopropane, 1,3-diaminopropane, 1,4-butanediamine, 1,5-diaminopentane, 1,6-diaminohexane (hexamethylenediamine), 1,7-diaminoheptane, 1,8-diaminooctane, 1,10-diaminodecane, 1,12-diaminododecane, 3,3-diaminodipropylamine, tris(3-aminopropyl)amine, 3,3'-diaminobenzidine, 1,4-cyclohexadiamine, spermine, spermidine, triethylenetetramine, 1,4-phenylenediamine, 1,2-diphenylethylenediamine, and orthotolidine.

[0039] Examples of the divalent or higher isocyanate include hexamethylene diisocyanate (HDI), pentamethylene diisocyanate (PDI), isophorone diisocyanate (IPDI), cyclohexane-1,4-diisocyanate, methylene bis(4-cyclohexyl isocyanate), toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymeric MDI, xylene diisocyanate, and 1,4-phenylene diisocyanate.

[0040] The anionic polymer compound B may be a commercially available product or a synthesized product. An example of a commercially available product is Z-221 (GOO Chemical Industry Co., Ltd.). When synthesizing the anionic polymer compound B, it may be obtained by a polymerization reaction using a monomer having a monovalent anionic group or a functional group that can be converted into an anionic group by carrying out an appropriate treatment, or by a reaction between a polymer compound containing a repeating unit having a reactive site and a compound (hereinafter also referred to as compound b) that is reactive to the reactive site and has a monovalent anionic group or a functional group that can be converted into a monovalent anionic group by carrying out an appropriate treatment.

[0041] Specific examples of the monomer include sodium 5-sulfoisophthalate, sodium 4-sulfoisophthalate, 4-sulfonaphthalene-2,6-dicarboxylic acid, monomethyl trimellitate, pyromellitic dianhydride, 4,4'-biphthalic anhydride, methacrylic acid, methyl methacrylate, and styrenesulfonic acid.

[0042] The polymerization reaction using the monomer includes polycondensation and polyaddition of the monomer with a divalent or higher carboxylic acid, a divalent or higher alcohol, a divalent or higher amine, a divalent or higher isocyanate, etc. The divalent or higher carboxylic acid, the divalent or higher alcohol, the divalent or higher amine, and the divalent or higher isocyanate are the same as those described above. The polymerization reaction is preferably, for example, polycondensation with sodium 5-sulfoisophthalate, terephthalic acid, and 1,4-butanediol, or polyaddition of pyromellitic dianhydride and hexamethylenediamine. In this case, in order to facilitate the reaction, a derivative of each raw material may be used instead of the raw material. In addition, a base catalyst such as DBU or triethylamine, or a metal catalyst such as dibutyltin dilaurate or titanium tetraisopropoxide may be used in the reaction.

[0043] Examples of polymer compounds containing a repeating unit having a reactive site include unsaturated polymer compounds containing a repeating unit having an aliphatic unsaturated carbon-carbon bond, such as unsaturated polyester compounds, unsaturated polyamide compounds, and unsaturated polyurethane compounds. These unsaturated polymer compounds can be synthesized by using unsaturated polyvalent carboxylic acids such as maleic acid, fumaric acid, citraconic acid, mesaconic acid, 2-pentenedioic acid, methylenesuccinic acid, allylmalonic acid, isopropylidenesuccinic acid, 2,4-hexadienedioic acid, and acetylenedicarboxylic acid, unsaturated polyvalent alcohols such as 2-butene-1,4-diol and 3-hexene-1,6-diol, unsaturated polyvalent amines such as 2-butene-1,4-diamine and 3-hexene-1,6-diamine, and unsaturated polyvalent isocyanates such as 2-butene-1,4-diisocyanate and 3-hexene-1,6-diisocyanate, together with the divalent or higher carboxylic acids, divalent or higher alcohols, divalent or higher amines, and divalent or higher isocyanates. Preferred examples include unsaturated polyesters obtained by polycondensation of maleic acid and 1,4-butanediol, and unsaturated polyamides obtained by polycondensation of sebacic acid, maleic acid, and hexamethylenediamine. In this case, in order to facilitate the progress of the reaction, derivatives of the respective raw materials may be used instead of the raw materials. In addition, in the reaction, a base catalyst such as DBU or triethylamine, or a metal catalyst such as dibutyltin dilaurate or titanium tetraisopropoxide may be used. In addition to the unsaturated polymer compounds, a radical initiator or radiation may be applied to a polyolefin-based polymer or a polyether-based polymer to produce a polymer compound having a radical site temporarily in the system.

[0044] Among the compounds b, compounds having reactivity with aliphatic unsaturated carbon-carbon bonds include mercaptocarboxylic acids such as 3-mercaptopropionic acid, amino acids such as 5-aminovaleric acid and 6-aminohexanoic acid, aminosulfonic acids such as 2-aminoethanesulfonic acid, aminophosphoric acids such as ethanolamine phosphoric acid, malonic acid, organic copper ate complexes, and other nucleophilic organic acids and derivatives thereof when the reaction with the unsaturated bond is a conjugate addition reaction, carboxylic acids and sulfonic acids having unsaturated bonds such as acrylic acid, 3-pentenoic acid, carboxystyrene, and styrenesulfonic acid when the reaction with the unsaturated bond is a radical reaction, pyrrole carboxylic acids such as 1-methyl-2-pyrrole carboxylic acid when the reaction with the unsaturated bond is a Diels-Alder reaction, and carboxylic acids having unsaturated bonds such as acrylic acid and 3-pentenoic acid when the reaction with the unsaturated bond is a photocycloaddition reaction. Among the compounds b, compounds having reactivity with radical sites include carboxylic acids and sulfonic acids having unsaturated bonds such as acrylic acid, 3-pentenoic acid, carboxystyrene, and styrenesulfonic acid.

[0045] The reaction between the polymer compound containing a repeating unit having the reactive site and the compound b is not particularly limited, but in consideration of reactivity, selectivity, physical properties of the product, and safety, it is preferable to use 3-mercaptopropionic acid, 5-aminovaleric acid, 6-aminohexanoic acid, or a malonic acid derivative in the conjugate addition reaction, and it is most preferable to use 3-mercaptopropionic acid in the conjugate addition reaction. In the reaction, a commonly used catalyst may be used as necessary, for example, a base catalyst such as DBU or TEA in the conjugate addition reaction, a transition metal catalyst such as an organic ruthenium complex or an organic titanium complex in the radical reaction, a Lewis acid catalyst such as ytterbium triflate or scandium triflate in the Diels-Alder reaction, and a photosensitizer such as thiophene or benzophenone in the photocycloaddition reaction. In this case, a derivative thereof may be used instead of each raw material in order to facilitate the reaction.

[0046] [Marine biodegradable polymer compounds] The marine biodegradable polymer compound of the present invention is one in which an anionic polymer compound A and an anionic polymer compound B are bonded via a divalent or higher metal cation.

[0047] The divalent or higher metal cation is not particularly limited, but may be calcium ion, beryllium ion, magnesium ion, strontium ion, barium ion, zinc ion, aluminum ion, iron ion, copper ion, platinum ion, gold ion, titanium ion, nickel ion, cobalt ion, manganese ion, zirconium ion, ruthenium ion, rhodium ion, palladium ion, scandium ion, gallium ion, indium ion, radium ion, etc. Among these, calcium ion, beryllium ion, magnesium ion, strontium ion, barium ion, zinc ion, aluminum ion, etc. are preferred, and calcium ion, magnesium ion, aluminum ion, etc. are more preferred. The divalent or higher metal cation may be used alone or in combination of multiple types.

[0048] The marine biodegradable polymer compound of the present invention may contain only one type of anionic polymer compound A and one type of anionic polymer compound B, or may contain multiple different types of anionic polymer compounds A and B, and may further contain other anions other than these. Examples of other anions include polyvalent anions, fatty acid anions, amino acid anions, amino acid derivative anions, and sulfonate anions.

[0049] Examples of the polyvalent anion include anions of 1,5-naphthalenedisulfonic acid, ethanedisulfonic acid, monoethyl phosphate, malic acid, aspartic acid, glutamic acid, succinic acid, adipic acid, sebacic acid, terephthalic acid, and isophthalic acid.

[0050] Examples of the fatty acid anions include anions of caproic acid, enanthic acid, caprylic acid, octylic acid, pelargonic acid, capric acid, undecylenic acid, lauric acid, myristic acid, pentadecylic acid, palmitic acid, palmitoleic acid, margaric acid, stearic acid, isostearic acid, oleic acid, vaccenic acid, ricinoleic acid, linoleic acid, linolenic acid, eleostearic acid, oxystearic acid, arachidic acid, mead acid, arachidonic acid, eicosapentaenoic acid, behenic acid, docosahexaenoic acid, lignoceric acid, nervonic acid, cerotic acid, montanic acid, melissic acid, coconut oil fatty acid, and palm oil fatty acid.

[0051] Examples of the amino acid anion or amino acid derivative anion include anions of amino acids such as alanine, leucine, arginine, lysine, asparagine, methionine, aspartic acid, phenylalanine, cysteine, proline, glutamine, serine, glutamic acid, threonine, glycine, tryptophan, histidine, tyrosine, and isoleucine, and anions of sarcosine derivatives (caproyl sarcosine, lauroyl sarcosine, myristoyl sarcosine, paclitaxel, etc.). lauroyl sarcosine, coconut oil fatty acid sarcosine, etc.), glutamic acid derivatives (caproyl glutamic acid, lauroyl glutamic acid, myristoyl glutamic acid, palmitoyl glutamic acid, stearoyl glutamic acid, coconut oil fatty acid acyl glutamic acid, cocoyl glutamic acid, acyl glutamic acid, dilauroyl glutamic acid, etc.), glycine derivatives (lauroyl glycine, myristoyl glycine, palmitoyl glycine, palmitoyl methyl glycine, etc.), Examples of anions include anions of amino acid derivatives having a hydrocarbon group, such as lysine, coconut oil fatty acid acylglycine, cocoylglycine, etc., alanine derivatives (lauryl methylalanine, myristoyl methylalanine, cocoyl alanine, coconut oil fatty acid methylalanine, etc.), lysine derivatives (lauroyl lysine, myristoyl lysine, palmitoyl lysine, stearoyl lysine, oleyl lysine, acylated lysine, etc.), aspartic acid derivatives (lauroyl aspartic acid, myristoyl aspartic acid, palmitoyl aspartic acid, stearoyl aspartic acid, etc.), taurine derivatives (lauroyl taurine, lauroyl methyl taurine, myristoyl taurine, myristoyl methyl taurine, palmitoyl taurine, palmitoyl methyl taurine, stearoyl taurine, stearoyl methyl taurine, etc.), and proline derivatives (lauroyl proline, myristoyl proline, palmitoyl proline, etc.).

[0052] Examples of the sulfonate anion include anions of alkyl sulfonic acid (lauryl sulfonic acid, myristyl sulfonic acid, cetyl sulfonic acid, stearyl sulfonic acid, oleyl sulfonic acid, etc.), dodecylbenzene sulfonic acid, dialkyl succinate sulfonic acid, monoalkyl succinate sulfonic acid, naphthalene sulfonic acid, olefin sulfonic acid, alkyl isethionic acid (lauroyl isethionic acid, myristoyl isethionic acid, palmitoyl isethionic acid, stearoyl isethionic acid, etc.), and dialkyl sulfosuccinic acid (dihexyl sulfosuccinic acid, dioctyl sulfosuccinic acid, didecyl sulfosuccinic acid, diisobutyl sulfosuccinic acid, etc.).

[0053] The metal ion equivalent (content of divalent or higher metal cations) in the marine biodegradable polymer compound is 1 to 300 eq / 10 5 g is preferable, but considering biodegradability in seawater and mechanical properties, 10 to 200 eq / 10 5 g is more preferable, and 20 to 100eq / 10 5 g is more preferable. If the metal ion equivalent is within the above range, it is preferable because it has good biodegradability and mechanical properties are not impaired. The metal ion equivalent is a value measured by inductively coupled plasma mass spectrometry (ICP-MS).

[0054] The marine biodegradable polymer compound can be an amorphous or crystalline polymer compound depending on the blending ratio of the anionic polymer compound A and the anionic polymer compound B. The marine biodegradable polymer compound is solid at room temperature, and specifically, the lower limit of the softening point is preferably 0°C or more, 40°C or more, and 80°C or more, in that order, and the upper limit is preferably 250°C or less, 200°C or less, 180°C or less, and 160°C or less, in that order. It is preferable that the softening point is within a range of preferably 40 to 200°C, more preferably 60 to 180°C, and even more preferably 80 to 160°C.

[0055] The marine biodegradable polymer compound preferably has a relative cellulose biodegradability of 40% or more, more preferably 50% or more, even more preferably 60% or more, and most preferably 80% or more.

[0056] [Production method of marine biodegradable polymer compound] The marine biodegradable polymer compound can be produced by a method including a step of crosslinking anionic polymer compound A and anionic polymer compound B using a divalent or higher metal salt (hereinafter also referred to as a polyvalent metal salt).

[0057] Examples of the crosslinking method include a method of dropping a powder, solution, or dispersion of a polyvalent metal salt into a solution or dispersion containing an anionic polymer compound A and an anionic polymer compound B, and precipitating or precipitating while performing a bonding treatment, a method of dropping a powder, solution, or dispersion of a polyvalent metal salt into a melt of anionic polymer compound A and anionic polymer compound B, and performing a bonding treatment, and a method of dropping a solution or dispersion containing an anionic polymer compound A and an anionic polymer compound B into a solution or dispersion in which a powder of a polyvalent metal salt or a polyvalent metal salt is dissolved, and precipitating or precipitating while performing a bonding treatment. These methods may be performed alone or in combination.

[0058] As a preferred example, first, a solution in which anionic polymer compound A and anionic polymer compound B are dissolved in water, an organic solvent, or a mixed solvent thereof, or a melt in which anionic polymer compound A and anionic polymer compound B are heated and dissolved is prepared. At this time, heating may be performed as necessary to improve solubility or reduce the viscosity of the melt. Next, a solution containing a polyvalent metal salt is added to the obtained solution or melt and stirred. Alternatively, a solution or melt in which anionic polymer compound A and anionic polymer compound B are dissolved may be added to a solution containing a polyvalent metal salt and stirred.

[0059] Examples of the polyvalent metal salt include calcium salt, strontium salt, magnesium salt, barium salt, radium salt, lead salt, zinc salt, nickel salt, iron salt, copper salt, cadmium salt, cobalt salt, manganese salt, aluminum salt, gallium salt, indium salt, and thallium salt. However, calcium salt, magnesium salt, and aluminum salt are preferred from the viewpoints of being metals contained in seawater, environmental aspects, safety, and versatility, and calcium salt and magnesium salt are more preferred in consideration of the seawater environment. Specific examples of the polyvalent metal salt include calcium chloride, calcium sulfate, calcium carbonate, calcium hydroxide, calcium oxide, magnesium chloride, magnesium sulfate, magnesium carbonate, magnesium hydroxide, magnesium oxide, aluminum sulfate, sodium aluminum sulfate (sodium alum), and potassium aluminum sulfate (potassium alum), and calcium chloride, magnesium chloride, and aluminum sulfate are preferred from the viewpoints of solubility in water, ease of handling, and cost.

[0060] The concentration of the polyvalent metal salt in the solution containing the polyvalent metal salt is preferably 1 to 40% by mass, more preferably 10 to 30% by mass. The solvent for the solution is preferably water, a lower alcohol solvent such as methanol, ethanol, 1-propanol, or 2-propanol, an amphipathic solvent such as acetone, acetonitrile, THF, DMF, DMSO, or NMP, or a mixed solvent thereof, but may be a mixed solvent with other organic solvents as long as the salt can be dissolved to a desired concentration without dissolving the resin.

[0061] In addition, if the polyvalent metal salt has a good reactivity and reacts even in a solid state, it may be used in a powder form without using a medium, or may be dispersed in a small amount of medium.

[0062] During crosslinking, for the purpose of controlling the particle size and shape (e.g., spherical shape) of the precipitate or sediment, a surfactant or a polymer stabilizer may be dissolved in at least one of the solution in which the anionic polymer compounds A and B are dissolved and the solution containing the polyvalent metal salt.

[0063] The method of preparing the solution or dispersion containing the anionic polymer compound A and the anionic polymer compound B is not limited, but examples thereof include a method of mixing the monovalent salt of the anionic polymer compound A and the monovalent salt of the anionic polymer compound B with water or an organic solvent, and a method of mixing the acidic polymer compound A and the acidic polymer compound B in which the monovalent anionic group of the anionic polymer compound A and the monovalent anionic group of the anionic polymer compound B are bonded to protons with water or an organic solvent, and adding a monovalent base thereto. These methods may be carried out alone or in combination. In addition, when carried out in combination, the order is not particularly limited.

[0064] As the monovalent counter cation constituting the monovalent salt of the anionic polymer compound A and the monovalent salt of the anionic polymer compound B, a lithium ion, a sodium ion, a potassium ion, a rubidium ion, a cesium ion, a francium ion, an ammonium ion, a methylammonium ion, an ethylammonium ion, an anilinium ion, a pyridinium ion, a dimethylammonium ion, a diethylammonium ion, a trimethylammonium ion, a triethylammonium ion, and the like are preferable, and from the viewpoints of safety, environmental load, and operability, a sodium ion, a potassium ion, and an ammonium ion are more preferable, and a sodium ion and a potassium ion are even more preferable.

[0065] Examples of the monovalent base include lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium carbonate, sodium carbonate, potassium carbonate, lithium hydrogen carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, trisodium phosphate, tripotassium phosphate, lithium methoxide, sodium methoxide, potassium methoxide, lithium tert-butoxide, sodium tert-butoxide, potassium tert-butoxide, ammonia, methylamine, ethylamine, TEA, DBU, etc. Preferred are lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium carbonate, sodium carbonate, potassium carbonate, lithium hydrogen carbonate, sodium hydrogen carbonate, or potassium hydrogen carbonate, and in consideration of safety and environmental load, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium hydrogen carbonate, or potassium hydrogen carbonate is particularly preferred.

[0066] By adding a base containing a divalent or higher metal to water or an organic solvent containing the acidic polymer compound A and the acidic polymer compound B, it is possible to produce a marine biodegradable polymer compound in a chain reaction following the production of the anionic polymer compound A and the anionic polymer compound B.

[0067] Examples of the base containing a divalent or higher metal include magnesium hydride, strontium hydride, calcium hydride, barium hydride, magnesium methoxide, calcium methoxide, strontium methoxide, barium methoxide, magnesium hydroxide, calcium hydroxide, strontium hydroxide, barium hydroxide, magnesium oxide, strontium oxide, calcium oxide, barium oxide, magnesium carbonate, strontium carbonate, calcium carbonate, barium carbonate, magnesium hydrogen carbonate, strontium hydrogen carbonate, calcium hydrogen carbonate, barium hydrogen carbonate, and the like. From the viewpoints of solubility in water, reactivity, cost, and the like, calcium hydride, calcium methoxide, calcium hydroxide, and barium hydroxide are preferred, and calcium hydroxide is more preferred.

[0068] As a preferred example, a solution in which the acidic polymer compound A and the acidic polymer compound B are dissolved in water, an organic solvent, or a mixed solvent thereof, or a melt in which the acidic polymer compound A and the acidic polymer compound B are heated and dissolved is prepared. At this time, heating may be performed as necessary to improve the solubility or to reduce the viscosity of the melt. Next, a solution of a base containing a divalent or higher metal is added to the obtained solution or melt and stirred. Alternatively, a solution or melt in which the acidic polymer compound A and the acidic polymer compound B are dissolved may be added to a solution of a base containing a divalent or higher metal and stirred.

[0069] Examples of the base containing a divalent or higher metal include magnesium hydride, strontium hydride, calcium hydride, barium hydride, magnesium methoxide, calcium methoxide, strontium methoxide, barium methoxide, magnesium hydroxide, calcium hydroxide, strontium hydroxide, barium hydroxide, magnesium oxide, strontium oxide, calcium oxide, barium oxide, magnesium carbonate, strontium carbonate, calcium carbonate, barium carbonate, magnesium hydrogen carbonate, strontium hydrogen carbonate, calcium hydrogen carbonate, barium hydrogen carbonate, and the like. From the viewpoints of solubility in water, reactivity, cost, and the like, calcium hydride, calcium methoxide, calcium hydroxide, and barium hydroxide are preferred, and calcium hydroxide is more preferred.

[0070] In addition, anionic polymer compound A and anionic polymer compound B do not necessarily have to be crosslinked at the same time. For example, after a portion of one of the anionic polymer compounds is crosslinked, the other anionic polymer compound can be added and further crosslinked to obtain a marine biodegradable polymer compound.

[0071] By subjecting the anionic polymer compound A and the anionic polymer compound B to the crosslinking treatment, the anionic polymer compound A and the anionic polymer compound B can be bonded via a metal cation, and the target marine biodegradable polymer compound which gradually becomes insoluble is obtained as a precipitate, sediment or bulk. The treatment time is preferably 0.5 to 24 hours, more preferably 1 to 12 hours.

[0072] Heating may be performed when precipitating or precipitating the desired marine biodegradable polymer compound. Heating may be performed when mixing a solution in which anionic polymer compound A and anionic polymer compound B are dissolved or a melt of anionic polymer compound A and anionic polymer compound B with a solution containing a polyvalent metal salt, or when stirring after mixing, or both of these. Alternatively, heating may be performed when mixing a solution in which acidic polymer compound A and acidic polymer compound B are dissolved or a melt of acidic polymer compound A and acidic polymer compound B with a solution containing a base containing a divalent or higher metal, or when stirring after mixing, or both of these. The heating temperature is preferably 5 to 200°C, more preferably 10 to 150°C, and even more preferably 20 to 100°C.

[0073] After the treatment, the particles can be washed and dried as necessary to obtain a marine biodegradable polymer compound. Washing can be performed by a conventional method, for example, removing the solvent after the binding treatment, adding water, and centrifuging. Drying can be performed by a conventional method, for example, spray drying, vacuum drying, freeze drying, etc. The obtained marine biodegradable polymer compound may be surface-treated or pulverized to adjust the particle size using known equipment as necessary.

[0074] The marine biodegradable polymer compound may be one in which at least one of the monovalent anionic groups that is not bonded to the anionic polymer compound via a divalent metal cation is blocked with a blocking segment group.

[0075] By selecting the blocking segment group, in a single material and a composite material (marine biodegradable resin composition) using this material, it is possible to incorporate multiple effects such as adjustment of melting temperature and melt viscosity, adjustment of crystallinity, adjustment of microbial adhesion and biodegradability, adjustment of physical properties such as resin tensile strength, bending strength, and elasticity, improvement of compatibility with resin, adjustment of hydrophobicity, adjustment of water repellency, adjustment of adhesion, and adjustment of plasticity, and it is possible to improve both the biodegradability and physical properties of the marine biodegradable resin composition. Since it is desirable for the organic anion to be the blocking segment to have a structure having marine biodegradability, it is desirable to select a blocking segment group having marine biodegradability with a molecular weight of 5000 or less. For example, when emphasis is placed on the biodegradability rate in the ocean and the maintenance of average physical properties, a molecular weight of 2500 or less is preferable, and a molecular weight of 1000 or less is more preferable.

[0076] Specifically, the capping segment group preferably has a hydrocarbon group having 3 or more carbon atoms, more preferably has a hydrocarbon group having 6 or more carbon atoms, even more preferably has a hydrocarbon group having 10 or more carbon atoms, and most preferably has a hydrocarbon group having 12 or more carbon atoms. There are no particular limitations on the upper limit of the carbon number of the hydrocarbon group, but it is preferably 30 or less, more preferably 25 or less, and even more preferably 20 or less.

[0077] The blocking segment group is preferably an organic anion selected from a carboxylate anion having a hydrocarbon group with 3 or more carbon atoms, a sulfonate anion having a hydrocarbon group with 3 or more carbon atoms, a sulfate ester anion having a hydrocarbon group with 3 or more carbon atoms, and a phosphate ester anion having a hydrocarbon group with 3 or more carbon atoms. Among these, a monovalent organic anion derived from a carboxylic acid having a hydrocarbon group with 3 or more carbon atoms is preferred, and a monovalent organic anion derived from a fatty acid having a hydrocarbon group with 3 or more carbon atoms or an amino acid derivative having a hydrocarbon group with 3 or more carbon atoms is more preferred.

[0078] The terminal blocking can be carried out using at least one terminal blocking agent selected from a carboxylic acid having a hydrocarbon group with 3 or more carbon atoms, a salt of the carboxylic acid, a sulfonic acid having a hydrocarbon group with 3 or more carbon atoms, a salt of the sulfonic acid, a sulfate ester having a hydrocarbon group with 3 or more carbon atoms, a salt of the sulfate ester, a phosphate ester having a hydrocarbon group with 3 or more carbon atoms, and a salt of the phosphate ester. The terminal blocking can be carried out by adding the terminal blocking agent to a solution containing polymer compound A or B, and then performing a bonding treatment with a polyvalent metal ion.

[0079] As the terminal blocking agent, the acid compounds or salt compounds described in paragraphs

[0029] to

[0044] of JP2021-191810A are preferable.

[0080] [Marine biodegradable resin composition] The marine biodegradable resin composition of the present invention contains the marine biodegradable polymer compound.

[0081] The marine biodegradable polymer compound may be used as a main raw material, or may be used in combination with other resins as additives. The other resins are not particularly limited, but are preferably biodegradable resins. When used in combination with other resins as additives, the marine biodegradable polymer compound functions as a marine biodegradation promoter. In this case, the composite resin becomes a resin composition in which biodegradation in the ocean is promoted. In addition, in order to adjust the physical properties and handling properties of the resin composition, multiple types of resins can be used in combination as the other resins.

[0082] Examples of the other resins include polyethylene, polyester, polypropylene, polyethylene terephthalate, polystyrene, polyurethane, epoxy resin, chlorinated polyethylene resin, chlorinated polypropylene resin, modified nylon resin, phenol resin, silicone resin, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinylidene chloride, styrene-maleic acid resin, styrene-butadiene resin, butadiene resin, acrylonitrile-butadiene resin, poly(meth)acrylonitrile resin, (meth)acrylamide resin, bio-PET, bio-polyamide, bio-polycarbonate, bio-polyurethane, polyvinyl alcohol, polybutylene adipate / terephthalate, polyethylene terephthalate succinate, bio-polybutylene succinate, polylactic acid blend, starch blend polyester resin, polybutylene terephthalate succinate, polylactic acid, and polyhydroxyalkanoic acid. In consideration of the effect of reducing the burden on the environment and promoting marine biodegradability, resins with high biodegradability are particularly preferred.

[0083] In addition, examples of the biodegradable resin include resins whose raw material is derived from petroleum, such as polycaprolactone, poly(caprolactone / butylene succinate), polybutylene succinate (PBS), poly(butylene succinate / adipate) (PBSA), poly(butylene adipate / terephthalate) (PBAT), poly(butylene succinate / carbonate), polyethylene terephthalate copolymer, poly(ethylene terephthalate / succinate), poly(tetramethylene adipate / terephthalate), polyethylene succinate, polyvinyl alcohol, polyglycolic acid, glycolic acid / caprolactone copolymer, and glycolic acid / trimethylene carbonate copolymer; (polylactic acid / polybutylene succinate-based) block copolymer, (polylactic acid / polycaprolactone) copolymer, and (polylactic acid / polyether) copolymer. Resins whose raw materials are partially derived from biomass, such as polylactic acid blend PBAT, lactic acid / glycolic acid copolymer, biopolybutylene succinate, poly(butylene succinate / adipate), starch blend polyester resin, and poly(butylene terephthalate succinate); polyhydroxyalkanoic acid such as polyhydroxybutyrate, polyhydroxyvaleric acid, polyhydroxycaprylic acid, poly(hydroxybutyrate / hydroxyhexanoate) (PHBH), poly(3-hydroxybutyrate / 4-hydroxybutyrate) (P3HB4HB), and poly(hydroxybutyrate / hydroxyvaleric acid) (PHBV), and polylactic acid (PLA) are 100% derived from biomass; resins derived from natural polymers such as cellulose, cellulose acetate, cellulose ester resin, starch, esterified starch, and chitosan. These may be used alone or in combination of two or more.

[0084] Among these, it is preferable to combine the marine biodegradable polymer compound with a biodegradable resin selected from resins that are biodegradable in soil or compost but poorly biodegradable in the ocean, such as polycaprolactone, PBS, PBSA, PBAT, poly(tetramethylene adipate / terephthalate), poly(butylene succinate / carbonate), polyhydroxyalkanoic acids such as PHBH and PHBV, PLA, cellulose, starch, chitosan, and other natural polymer-derived resins. As the biodegradable resin, particularly preferred are resins derived from PBSA, PBS, PBAT, PLA, and starch.

[0085] In addition, in consideration of reducing the environmental burden, the raw materials for the resin to be combined are preferably at least 20% biomass-derived, more preferably at least 50% biomass-derived, and most preferably 100% biomass-derived raw materials.

[0086] The marine biodegradable resin composition of the present invention may contain a solvent. The solvent may dissolve the resin that serves as a matrix while leaving the marine biodegradable polymer compound as particles, or may dissolve both the resin and the marine biodegradable polymer compound. By appropriately adjusting these, the composition can be used as a molded body formed into a film by casting or the like, as a paint, ink, surface treatment agent, etc. Examples of preferred solvents include water, formic acid, hexane, heptane, acetonitrile, N-methylpyrrolidone, dimethylformamide, dimethylacetamide, dimethylsulfoxide, dimethylsulfone, acetone, methyl ethyl ketone, diethyl ketone, acetophenone, dimethyl ether, dipropyl ether, tetrahydrofuran, chloroform, methylene chloride (dichloromethane), trichloroethylene, ethylene dichloride, tetrachloroethane, chlorobenzene, methanol, ethanol, n-propanol, isopropanol, butanol, pentanol, hexafluoroisopropanol, methyl glycol, methyl triglycol, hexyl glycol, phenyl glycol, ethylene glycol, propylene glycol, phenol, cresol, polyethylene glycol, benzene, toluene, xylene, etc. These may be used alone or in combination of two or more.

[0087] When a solvent is used, the total concentration of the resin and the marine biodegradable polymer compound in the resin composition is preferably 0.5 to 90% by mass, more preferably 1 to 80% by mass, even more preferably 5 to 60% by mass, and most preferably 10 to 50% by mass. The ratio of the marine biodegradable polymer compound to the resin is preferably 99:1 to 10:90, more preferably 97:3 to 40:60, even more preferably 95:5 to 50:50, and most preferably 90:10 to 60:40, by mass.

[0088] The lower limit of the softening point of the resin composition is preferably 60° C. or more, 70° C. or more, and 80° C. or more, in that order, and the upper limit is preferably 300° C. or less, 250° C. or less, 200° C. or less, and 180° C. or less, in that order. The softening point is preferably in the range of 60 to 250° C., more preferably 70 to 200° C., and even more preferably 80 to 180° C.

[0089] The marine biodegradable resin composition of the present invention may not contain a solvent. In this case, the resin may be thermally melted and a non-melting marine biodegradable polymer compound may be added thereto and mixed, or the resin and the marine biodegradable polymer compound may be melted together and mixed.

[0090] In the marine biodegradable resin composition of the present invention, the content of the marine biodegradable polymer compound is preferably 1 to 60 mass%, more preferably 3 to 50 mass%, more preferably 5 to 45 mass%, even more preferably 7 to 40 mass%, and most preferably 10 to 35 mass%. On the other hand, the content of the resin is preferably 40 to 99 mass%, more preferably 50 to 97 mass%, even more preferably 55 to 95 mass%, even more preferably 60 to 93 mass%, and most preferably 65 to 90 mass%. By containing the marine biodegradable polymer compound in the above range, the composition can be utilized as a marine biodegradation promoter that promotes biodegradation in seawater while maintaining the physical properties of the biodegradable resin. The marine biodegradable polymer compound may be used alone or in combination of two or more.

[0091] The tensile strength of the test piece obtained from the resin composition is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more when the content of the marine biodegradable polymer compound in the resin composition is 10% by mass, compared to a blank resin test piece not containing the marine biodegradable polymer compound of the present invention. When the content of the marine biodegradable polymer compound in the resin composition is 30% by mass, the tensile strength is preferably 65% ​​or more, more preferably 70% or more, and even more preferably 80% or more.

[0092] The marine biodegradable resin composition of the present invention may contain additives such as antioxidants, release agents, peeling agents, surface modifiers, hydrophobic agents, water repellents, hydrophilizing agents, dyes and pigments, colorants, heat stabilizers, light stabilizers, weather resistance improvers, antistatic agents, antifogging agents, lubricants, antiblocking agents, hardeners, softeners, compatibilizers, flame retardants, flow improvers, plasticizers, dispersants, antibacterial agents, fillers, metal deactivators, etc. The content of these additives is not particularly limited as long as it does not impair the effects of the present invention, but is preferably about 0.1 to 50 parts by mass relative to 100 parts by mass of the resin.

[0093] When the marine biodegradable resin composition contains a solvent, it can be prepared, for example, by adding the resin, the marine biodegradable polymer compound, and the additives, if necessary, to a solvent simultaneously or in any order, and mixing them. When the marine biodegradable resin composition does not contain a solvent, it can be prepared, for example, by melting the resin, adding the marine biodegradable polymer compound and the additives, if necessary, to the solvent simultaneously or in any order, and mixing them, or by heating the resin and the marine biodegradable polymer compound to melt them together and mix them, and adding the additives, if necessary, and mixing them.

[0094] [Molded body] By molding the resin composition, a molded article in which the marine biodegradable polymer compound is dispersed or dissolved in the resin can be obtained. When the resin composition contains a solvent, the resin composition can be used as is for molding, and when the resin composition does not contain a solvent, the resin or the resin and the marine biodegradable polymer compound in the resin composition can be melted by heat and then molded.

[0095] The shape of the molded product may be, for example, a film, a fiber, a plate, a foam molded product, or any other shape depending on the application. The molding method is not particularly limited, and any of the conventionally known molding methods may be used. Specific examples of such methods include blow molding, injection molding, extrusion molding, compression molding, melt extrusion molding, solution casting molding, and calendar molding.

[0096] [Application] The marine biodegradable polymer compound and marine biodegradable resin composition of the present invention can be used as a raw material for plastic molded products, and as various additives for molded products such as liquids, coatings, films, plates, paper, etc. When used as a raw material for plastic molded products, it can be used as a raw material for general-purpose applications such as films, packaging, containers, trays, laminate materials, adhesives, coating materials, medical materials, fibers for clothing, shoes, belts, tires, tubes, shock absorbing materials, fishing lines, fishing nets, etc., and materials for marine applications, etc., and can be particularly preferably used as a raw material for marine applications, etc. In addition, when used as an additive, for example, light scattering agents and optical filter materials, colorants, cosmetics, absorbents, adsorbents, inks, adhesives, electromagnetic wave shielding materials, fluorescent sensors, biomarkers, recording materials, recording elements, polarizing materials, drug carriers for drug delivery systems (DDS), biosensors, DNA chips, test agents, baked voided molded products, antiblocking agents, screen printing, offset printing, process printing, gravure printing, pad printing, coaters, inkjet printing, etc., additives for printing inks used in marking pens, ballpoint pens, fountain pens, brush pens, markers, and other writing instrument ink additives, crayons, paints, erasers, and other stationery additives, paint additives used in brush painting, spray painting, electrostatic painting, electrocoating, flow painting, roller painting, dip painting, etc., and especially paints used for marine applications such as hull paints. It can be widely used as an additive. EXAMPLES

[0097] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In the following examples and comparative examples, the metal ion equivalent was measured by heating and decomposing the target substance with nitric acid or aqua regia, and then measuring the metal ion equivalent by emission spectrometry using an ICP-MS (ICPE-9820, manufactured by Shimadzu Corporation). The number average molecular weight and the number of anionic groups were measured using a nuclear magnetic resonance apparatus (JNM-ECZ400S, manufactured by JEOL Ltd.). 1 It was calculated from the peak integral value in H-NMR.

[0098] [1] Synthesis of anionic polymer compound A [Synthesis Example 1-1] Synthesis of anionic polymer compound A-1 In a 1000 mL reaction vessel, 400 g of polyester diol (Kuraray Polyol P-1010 manufactured by Kuraray Co., Ltd.), 84 g of succinic anhydride, and 40 g of acetonitrile were charged, and the mixture was stirred for 2 hours at 130° C. under a nitrogen atmosphere to obtain an acidic polymer compound A-1. In a 3000 mL recovery flask, 500 g of acidic polymer compound A-1, 412 g of water, and 88 g of potassium bicarbonate were added, and the mixture was stirred at room temperature to obtain an anionic polymer compound A-1. The aniline polymer compound A-1 is linear and has monovalent anionic groups at both ends thereof. 1 The number average molecular weight was confirmed to be 1,300 by H-NMR measurement.

[0099] [Synthesis Example 1-2] Synthesis of anionic polymer compound A-2 In a 1000 mL reaction vessel, 400 g of polyester triol (Kuraray Polyol F-1010 manufactured by Kuraray Co., Ltd.), 126 g of succinic anhydride, and 60 g of acetonitrile were charged, and the mixture was stirred for 2 hours at 130° C. under a nitrogen atmosphere to obtain an acidic polymer compound A-2. In a 3000 mL recovery flask, 500 g of acidic polymer compound A-2, 368 g of water, and 132 g of potassium bicarbonate were added, and the mixture was stirred at room temperature to obtain an anionic polymer compound A-2. The aniline polymer compound A-2 is a branched polymer having three branches, and has monovalent anionic groups at all of its terminals. 1 The number average molecular weight was confirmed to be 1,400 by H-NMR measurement.

[0100] [Synthesis Example 1-3] Synthesis of anionic polymer compound A-3 In a 1000 mL eggplant flask, 130 g of 1,4-butanediol, 71 g of dimethyl terephthalate, 150 g of dimethyl adipate, and 2.4 g of titanium tetraisopropoxide were added, and the mixture was stirred at 160° C. for 6 hours under a nitrogen atmosphere, and then 32 g of succinic anhydride and 40 g of acetonitrile were added, and the mixture was stirred at 130° C. for 2 hours to obtain an acidic polymer compound A-3. In a 3000 mL eggplant flask, 350 g of acidic polymer compound A-3, 316 g of water, and 34 g of potassium bicarbonate were added, and the mixture was stirred at 80° C. to obtain an anionic polymer compound A-3. The aniline polymer compound A-3 is linear and has monovalent anionic groups at both ends thereof. 1 The number average molecular weight was confirmed to be 2,300 by H-NMR measurement.

[0101] [Synthesis Example 1-4] Synthesis of anionic polymer compound A-4 In a 1000mL eggplant flask, 280g of hexamethylenediamine, 340g of sebacic acid and 80g of water were added, and the mixture was put into an autoclave and fully substituted with nitrogen, and then heated to 230°C while stirring. After stirring at 230°C for 1 hour while maintaining the sealed state, the pressure was released to normal pressure, and the solid content was washed with ethanol and dried. 400g of the dried resin was crushed, and 82g of succinic anhydride, 100g of potassium carbonate and 400g of acetonitrile were added, and the mixture was stirred at 70°C for 4 hours, after which the reaction solution was cooled to room temperature and a precipitate was precipitated. The precipitate was removed by filtration, and the resulting filtrate was concentrated under reduced pressure to obtain an acidic polymer compound A-4. Finally, 300g of acidic polymer compound A-4, 263g of water and 37g of potassium hydrogen carbonate were added to a 3000mL eggplant flask and stirred at 80°C to obtain an anionic polymer compound A-4. The aniline polymer compound A-4 is linear and has monovalent anionic groups at both ends thereof. 1 The number average molecular weight was confirmed to be 1,800 by H-NMR measurement.

[0102] [Synthesis Example 1-5] Synthesis of anionic polymer compound A-5 In a 1000 mL reaction vessel, 300 g of polyether diol (polytetramethylene ether glycol manufactured by Mitsubishi Chemical Corporation), 94 g of succinic anhydride, and 30 g of acetonitrile were charged and stirred for 2 hours at 130° C. under a nitrogen atmosphere to obtain an acidic polymer compound A-5. In a 3000 mL recovery flask, 400 g of acidic polymer compound A-5, 1100 g of water, and 100 g of potassium bicarbonate were added and stirred at room temperature to obtain an anionic polymer compound A-5. The aniline polymer compound A-5 is linear and has monovalent anionic groups at both ends thereof. 1 The number average molecular weight was confirmed to be 900 by H-NMR measurement.

[0103] The anionic polymer compounds A-1 to A-5 are shown in Table 1 below.

[0104] [Table 1]

[0105] [2] Synthesis of anionic polymer compound B

[0106] [Synthesis Example 2-1] Synthesis of anionic polymer compound B-1 204 g of ethylene glycol, 80 g of dimethyl terephthalate, 122 g of sodium dimethyl 5-sulfoisophthalate, and 1.0 g of titanium tetraisopropoxide were added to a 1000 mL recovery flask, and the mixture was stirred at 200° C. for 3 hours under a nitrogen atmosphere. The liquid was then distilled off under reduced pressure to obtain anionic polymer compound B-1. The anionic polymer compound B-1 is 1 H-NMR measurement confirmed that the number-average molecular weight was 3,000 and that the polymer had an average of six monovalent anionic groups in the side chains.

[0107] [Synthesis Example 2-2] Synthesis of anionic polymer compound B-2 In a 1000 mL recovery flask, 142 g of ethylene glycol, 110 g of dimethyl sebacate, 142 g of sodium dimethyl 5-sulfoisophthalate, and 0.7 g of titanium tetraisopropoxide were added, and the mixture was stirred at 200° C. for 3 hours under a nitrogen atmosphere to obtain anionic polymer compound B-2. The anionic polymer compound B-2 is 1 H-NMR measurement confirmed that the number average molecular weight was 1500 and that the polymer had an average of three monovalent anionic groups in the side chains.

[0108] [Synthesis Example 2-3] Synthesis of anionic polymer compound B-3 195 g of 1,4-butanediol, 110 g of dimethyl adipate, 80 g of sodium dimethyl 5-sulfoisophthalate, and 0.9 g of titanium tetraisopropoxide were added to a 1000 mL recovery flask, and the mixture was stirred at 200° C. for 3 hours under a nitrogen atmosphere to obtain anionic polymer compound B-3. The anionic polymer compound B-3 is 1 H-NMR measurement confirmed that the number average molecular weight was 1900 and that the polymer had an average of three monovalent anionic groups in the side chains.

[0109] [Synthesis Example 2-4] Synthesis of anionic polymer compound B-4 In a 1000 mL recovery flask, 11 g of hexamethylenediamine and 160 g of tetrahydrofuran were added, and then a solution of 25 g of pyromellitic anhydride and 200 g of tetrahydrofuran was gradually added, and the mixture was stirred for 2 hours at 50° C. under a nitrogen atmosphere. After distilling off the solvent, 22 g of potassium hydrogen carbonate and 200 g of water were added, and the mixture was stirred at room temperature to obtain an anionic polymer compound B-4. The anionic polymer compound B-4 is 1 H-NMR measurement confirmed that the number-average molecular weight was 2000 and that the polymer had an average of 13 monovalent anionic groups in the side chains.

[0110] [Synthesis Example 2-5] Synthesis of anionic polymer compound B-5 In a 1000 mL recovery flask, 119.1 g of 1,4-butanediol, 75.6 g of succinic acid, and 25.0 g of maleic acid were added, and the mixture was stirred at 160°C for 6 hours under a nitrogen atmosphere. After that, 90.1 g of 3-mercaptopropionic acid and 34.4 g of acetonitrile were added, and the mixture was stirred at 130°C for 4 hours to obtain anionic polymer compound B-5. The anionic polymer compound B-5 is 1 It was confirmed by 1 H-NMR measurement that the number average molecular weight was 1800 and that the copolymer had an average of three monovalent anionic groups.

[0111] The anionic polymer compounds B-1 to B-5 are summarized in Table 2 below.

[0112] [Table 2]

[0113] [3] Biodegradability test of anionic polymer compounds [Reference examples 1~10] The anionic polymer compounds A-1 to A-5 and the anionic polymer compounds B-1 to B-5 were subjected to a seawater biodegradation test by the following method. As a control material, microcrystalline cellulose (Avicel PH-101 manufactured by Sigma-Aldrich) was used and evaluated by the relative biodegradability of cellulose. The results are shown in Table 4.

[0114] <Test method and conditions> Biodegradability measurement method: Measurement of oxygen consumption using a closed respirometer (ASTM D6691 reference) Test equipment: OxiTop IDS (WTW) Culture temperature: 30±1℃, dark place Biodegradation degree (%)=(BOD O -BOD B ) / ThOD×100 BOD O : Biochemical oxygen demand for testing or inoculum activity confirmation (measured value: mg) BOD B : Average biochemical oxygen demand in blank test (measured value: mg) ThOD: required when the test or control material is completely oxidized Theoretical oxygen demand (calculated value: mg) Relative biodegradability of cellulose (%) = (maximum biodegradability of test particles / maximum biodegradability of cellulose) x 100 Seawater (collected from Tokyo Bay [Chiba Prefecture: Chiba Port])] The collected seawater was aerated at room temperature of 25 degrees Celsius after removing foreign matter with a 10 μm filter. In addition, ammonium chloride and potassium dihydrogen phosphate were added as inorganic nutrients at 0.05 g / L and 0.1 g / L, respectively.

[0115] [Table 3]

[0116] From the results shown in Table 3, anionic polymer compound A and anionic polymer compound B were found to be biodegradable, with the relative degree of cellulose decomposition reaching 40% or more within a culture period of 60 days.

[0117] [4] Synthesis of marine biodegradable polymer compounds [Example 1-1] Synthesis of marine biodegradable polymer compound C-1 In a 1000 mL eggplant flask, 400 g of 25% by mass anionic polymer compound A-1 aqueous solution and 100 g of 25% by mass anionic polymer compound B-1 aqueous solution were added and thoroughly stirred until homogenized. Then, 140 g of 30% by mass calcium chloride aqueous solution was added and stirred to produce a precipitate. The precipitate was washed with water and then dried under reduced pressure to obtain marine biodegradable polymer compound C-1.

[0118] [Example 1-2] Synthesis of marine biodegradable polymer compound C-2 In a 1000mL eggplant flask, 200g of 50% by mass anionic polymer compound A-2 aqueous solution and 400g of 25% by mass anionic polymer compound B-2 aqueous solution were added and thoroughly stirred until homogenous. Then, 175g of 30% by mass calcium chloride aqueous solution was added and stirred to produce a precipitate. The precipitate was washed with water and then dried under reduced pressure to obtain marine biodegradable polymer compound C-2.

[0119] [Example 1-3] Synthesis of marine biodegradable polymer compound C-3 In a 1000mL eggplant flask, 160g of 50% by mass anionic polymer compound A-3 aqueous solution and 480g of 25% by mass anionic polymer compound B-3 aqueous solution were added and stirred until homogenous. Then, 120g of 30% by mass magnesium chloride aqueous solution was added and stirred to produce a precipitate. The precipitate was washed with water and then dried under reduced pressure to obtain marine biodegradable polymer compound C-3.

[0120] [Examples 1-4] Synthesis of marine biodegradable polymer compound C-4 In a 1000 mL eggplant flask, 320 g of 50% by mass anionic polymer compound A-4 aqueous solution and 160 g of 25% by mass anionic polymer compound B-1 aqueous solution were added and thoroughly stirred until homogenous. Then, 110 g of 30% by mass calcium chloride aqueous solution was added and stirred to produce a precipitate. The precipitate was washed with water and then dried under reduced pressure to obtain marine biodegradable polymer compound C-4.

[0121] [Examples 1-5] Synthesis of marine biodegradable polymer compound C-5 In a 2000 mL eggplant flask, 640 g of 50% by mass anionic polymer compound A-5 aqueous solution and 160 g of 25% by mass anionic polymer compound B-1 aqueous solution were added and thoroughly stirred until homogenous. Then, 320 g of 40% by mass aluminum sulfate aqueous solution was added and stirred to produce a precipitate. The precipitate was washed with water and then dried under reduced pressure to obtain marine biodegradable polymer compound C-5.

[0122] [Examples 1-6] Synthesis of marine biodegradable polymer compound C-6 In a 1000 mL eggplant flask, 160 g of 50% by mass anionic polymer compound A-1 aqueous solution and 480 g of 25% by mass anionic polymer compound B-4 aqueous solution were added and thoroughly stirred until homogenous. Then, 360 g of 30% by mass calcium chloride aqueous solution was added and stirred to produce a precipitate. The precipitate was washed with water and then dried under reduced pressure to obtain marine biodegradable polymer compound C-6.

[0123] [Examples 1-7] Synthesis of marine biodegradable polymer compound C-7 In a 1000mL eggplant flask, 120g of 50% by mass anionic polymer compound A-3 aqueous solution and 560g of 25% by mass anionic polymer compound B-5 aqueous solution were added and thoroughly stirred until homogenized. Then, 130g of 30% by mass calcium chloride aqueous solution was added and stirred to produce a precipitate. The precipitate was washed with water and then dried under reduced pressure to obtain marine biodegradable polymer compound C-7.

[0124] [Examples 1-8] Synthesis of marine biodegradable polymer compound C-8 In a 1000mL eggplant flask, 240g of 50% by mass anionic polymer compound A-1 aqueous solution, 80g of 50% by mass anionic polymer compound A-2 aqueous solution, and 160g of 25% by mass anionic polymer compound B-1 aqueous solution were added and thoroughly stirred until homogenized. Then, 160g of 30% by mass calcium chloride aqueous solution was added and stirred to produce a precipitate. The precipitate was washed with water and then dried under reduced pressure to obtain marine biodegradable polymer compound C-8.

[0125] [Examples 1-9] Synthesis of marine biodegradable polymer compound C-9 In a 1000mL eggplant flask, 320g of 50% by mass anionic polymer compound A-1 aqueous solution, 80g of 25% by mass anionic polymer compound B-1 aqueous solution, and 80g of 25% by mass anionic polymer compound B-3 aqueous solution were added and stirred until homogenous. Then, 130g of 30% by mass calcium chloride aqueous solution was added and stirred to produce a precipitate. The precipitate was washed with water and then dried under reduced pressure to obtain marine biodegradable polymer compound C-9.

[0126] [Comparative Example 1-1] Synthesis of marine biodegradable polymer compound X-1 In a 1000 mL recovery flask, 400 g of a 50% by mass anionic polymer compound A-2 aqueous solution was added, followed by 180 g of a 30% by mass calcium chloride aqueous solution, and the mixture was stirred to produce a precipitate. The precipitate was washed with water and then dried under reduced pressure to obtain marine biodegradable polymer compound X-1.

[0127] Table 4 below shows the marine biodegradable polymer compounds C-1 to C-9 and X-1.

[0128] [Table 4]

[0129] [4] Preparation of marine biodegradable resin composition and confirmation test in seawater-1 (1) Surface changes [Examples 2-1 to 2-9, Comparative Examples 2-1 to 2-2] Marine biodegradable polymer compounds C-1 to C-9 and X-1, which were crushed with a crusher (Osaka Chemical Co., Ltd. Wonder Blender WB-1) and classified with a stainless steel sieve (26 μm mesh), were melt-kneaded at 140°C to a concentration of 20% by mass, and press-molded at 150°C to produce a film with a thickness of 200 μm (Examples 2-1 to 2-9, Comparative Example 2-1). PBSA itself (not containing marine biodegradable polymer compounds) was press-molded at 150°C to produce a film with a thickness of 200 μm (Comparative Example 2-2). The obtained films were cut into 10 mm square pieces and placed in 200 mL of ion-exchanged water and 200 mL of seawater (collected from Tokyo Bay (Chiba Prefecture: Chiba Port)) at 25°C for 7 and 30 days, respectively, and then the films were taken out and the surface and appearance of the films were observed under a scanning electron microscope. The results are shown in Table 5.

[0130] [Table 5]

[0131] From the results shown in Table 5, it is considered that, in addition to the breakdown by seawater, biodegradation is also promoted by the presence of microorganisms in seawater.

[0132] (2) Weight loss of composite resin [Examples 3-1 to 3-9, Comparative Examples 3-1 to 3-2] Using the same method as in (1), films were prepared by adding marine biodegradable polymer compounds C-1 to C-9 and X-1 to PBSA, as well as a film of PBSA alone. The obtained films were processed into 20 mm squares, sandwiched between stainless steel nets, and immersed in seawater (collected from Tokyo Bay [Chiba Prefecture: Chiba Port]) in a 15 L tank, and the progress of weight loss after immersion for 30, 60, and 90 days was observed. The results are shown in Table 6.

[0133] [Table 6]

[0134] From the results shown in Table 6, it is believed that in addition to the breakdown by seawater, biodegradation is also promoted by the presence of microorganisms in seawater.

[0135] (3) Tensile strength measurement [Examples 4-1 to 4-9, Comparative Example 4-1] In the same manner as in (1), films were prepared by adding marine biodegradable polymer compounds C-1 to C-9 and X-1 to PBSA at concentrations of 10 mass%, 20 mass%, or 30 mass%, respectively, as well as a film of PBSA alone. In accordance with JIS K 7139-A22, dumbbells were prepared from the various films, and the tensile stress (yield point) was measured using a universal testing machine (MCT-2150, manufactured by A&D Co., Ltd.). Each sample was measured five times, and the average value was taken as the tensile stress. The results are shown in Table 7.

[0136] [Table 7]

[0137] From the results shown in Table 7, it was confirmed that the marine biodegradable polymer compound of the present invention has improved mechanical properties compared to X-1.

[0138] (4) Softening point measurement [Examples 5-1 to 5-9, Comparative Example 5-1] In the same manner as in (1), films were prepared by adding marine biodegradable polymer compounds C-1 to C-9 and X-1 to PBSA at concentrations of 10 mass%, 20 mass% or 30 mass%, respectively, and a film of PBSA alone. The softening points of the marine biodegradable polymer compounds C-1 to C-9 and X-1 were measured using a thermomechanical analyzer (TMA4000SE, manufactured by NETZSCH Japan Co., Ltd.). Specifically, a test piece having a thickness of 200 μm, a length of 150 mm and a width of 3 mm was pulled with a load of 10 g, and the temperature at which an elongation of 1 mm was observed in the temperature range of 0 to 180 ° C. (heating rate 3 ° C. / min) was taken as the softening point. The results are shown in Table 8.

[0139] [Table 8]

[0140] From the results shown in Table 8, it was confirmed that the marine biodegradable polymer compound of the present invention has improved thermal properties compared to X-1.

[0141] [5] Preparation of marine biodegradable resin composition and confirmation test in seawater-2 (1) Surface changes [Examples 6-1 to 6-9, Comparative Examples 6-1 to 6-2] Marine biodegradable polymer compounds C-1 to C-9 and X-1, which were crushed with a crusher (Wonder Blender WB-1 manufactured by Osaka Chemical Co., Ltd.) and classified with a stainless steel sieve (26 μm mesh size), were melt-kneaded at 140°C to a concentration of 20% by mass, and press-molded at 150°C to produce a film with a thickness of 200 μm (Examples 6-1 to 6-9, Comparative Example 6-1). In addition, the starch-based resin itself (not containing the marine biodegradable polymer compound) was press-molded at 150°C to produce a film with a thickness of 200 μm (Comparative Example 6-2). The obtained films were cut into 10 mm square pieces and placed in 200 mL of ion-exchanged water and 200 mL of seawater (collected from Tokyo Bay (Chiba Prefecture: Chiba Port)) at 25°C for 7 and 30 days, respectively, and then the films were taken out and the surface and appearance of the films were observed under a scanning electron microscope. The results are shown in Table 9.

[0142] [Table 9]

[0143] From the results shown in Table 9, it is considered that, in addition to the breakdown by seawater, biodegradation is also promoted by the presence of microorganisms in seawater.

[0144] (2) Weight loss of composite resin [Examples 7-1 to 7-9, Comparative Examples 7-1 to 7-2] In the same manner as in (1), films were prepared by adding marine biodegradable polymer compounds C-1 to C-9 and X-1 to starch-based resin, and a film of starch-based resin alone. The obtained films were processed into 20 mm squares, sandwiched between stainless steel nets, and immersed in seawater (collected from Tokyo Bay [Chiba Prefecture: Chiba Port]) in a 15 L tank, and the progress of weight loss after immersion for 30, 60, and 90 days was observed. The results are shown in Table 10.

[0145] [Table 10]

[0146] From the results shown in Table 10, it is believed that in addition to the breakdown by seawater, biodegradation is also promoted by the presence of microorganisms in seawater.

[0147] (3) Tensile strength measurement [Examples 8-1 to 8-9, Comparative Example 8-1] Using a method similar to that used in (1), films were prepared in which marine biodegradable polymer compounds C-1 to C-9 and X-1 were added to starch-based resin at concentrations of 10 mass%, 20 mass%, or 30 mass%, respectively, as well as films of starch-based resin alone. According to JIS K 7139-A22, dumbbells were made from various films and the tensile stress (yield point) was measured using a universal testing machine (MCT-2150, manufactured by A&D Co., Ltd.). Each sample was measured five times, and the average value was taken as the tensile stress. The results are shown in Table 11.

[0148] [Table 11]

[0149] From the results shown in Table 11, it was confirmed that the marine biodegradable polymer compound of the present invention has improved mechanical properties compared to X-1.

[0150] (4) Softening point measurement [Examples 9-1 to 9-9, Comparative Example 9-1] In the same manner as in (1), films were prepared by adding marine biodegradable polymer compounds C-1 to C-9 and X-1 to starch-based resin at concentrations of 10 mass%, 20 mass% or 30 mass%, respectively, and a film of starch-based resin alone. The softening points of marine biodegradable polymer compounds C-1 to C-9 and X-1 were measured using a thermomechanical analyzer (TMA4000SE, manufactured by NETZSCH Japan Co., Ltd.). Specifically, a test piece having a thickness of 200 μm, a length of 150 mm and a width of 3 mm was pulled with a load of 10 g, and the temperature at which an elongation of 1 mm was observed in the temperature range of 0 to 180 ° C. (heating rate 3 ° C. / min) was taken as the softening point. The results are shown in Table 12.

[0151] [Table 12]

[0152] From the results shown in Table 12, it was confirmed that the marine biodegradable polymer compound of the present invention has improved thermal properties compared to X-1.

[0153] From the above results, the marine biodegradable polymer compound of the present invention is likely to dissolve or become hydrophilic in seawater by being decomposed into lower molecules or salt-substituted by biodegradation prior to the biodegradable resin. Therefore, by adding a marine biodegradation promoter consisting of the marine biodegradable polymer compound of the present invention to a resin composition that is biodegradable in soil or compost or a resin composition that is poorly biodegradable in the sea, it becomes possible to form irregularities in seawater, aid the attachment of microorganisms, and promote biodegradation, which ultimately makes it possible to improve the overall marine biodegradability and reduce the environmental burden. By combining the marine biodegradation promoter consisting of the marine biodegradable polymer compound of the present invention with a resin that is biodegradable in soil or compost, it is possible to improve the seawater biodegradability, and by appropriately modifying the structure of the organic anion, it is possible to incorporate a number of effects, such as adjustment of the melting temperature and viscosity, adjustment of the degree of crystallinity, adjustment of microbial adhesion and biodegradability, adjustment of physical properties such as the resin tensile strength, flexural strength, and elasticity, improvement of compatibility with the resin, adjustment of the degree of hydrophobicity, adjustment of hydrophobicity, adjustment of adhesion and plasticity, etc., and it is possible to improve both the biodegradability and physical properties of the marine biodegradable resin composition.

Claims

1. A marine biodegradable polymer compound comprising an anionic polymer compound A having a linear or branched main chain, a total of two or more monovalent anionic groups at the ends of the main chain, and no ionic groups in the side chain, and an anionic polymer compound B having monovalent anionic groups in the side chains of two or more repeating units, bonded via a divalent or higher metal cation.

2. 2. The polymer compound according to claim 1, wherein the mass ratio of the anionic polymer compound A to the anionic polymer compound B is from 99:1 to 10:

90.

3. 2. The polymer compound according to claim 1, wherein the main chain of the anionic polymer compound A is linear.

4. 2. The polymer compound according to claim 1, wherein the anionic polymer compound B comprises a repeating unit having no ionic group.

5. 2. The polymer compound according to claim 1, wherein the anionic polymer compound B has an aliphatic unsaturated carbon-carbon bond in the main chain.

6. 2. The polymer compound according to claim 1, wherein the monovalent anionic group of the anionic polymer compound A is a carboxylate anion.

7. 2. The polymer compound according to claim 1, wherein the monovalent anionic group of the anionic polymer compound B is a carboxylate anion or a sulfonate anion.

8. 2. The polymer compound according to claim 1, wherein the monovalent anionic group of the anionic polymer compound B is bonded to a ring.

9. 2. The polymer compound according to claim 1, wherein the anionic polymer compound A has a number average molecular weight of 500 to 10,000, and the anionic polymer compound B has a number average molecular weight of 500 to 10,000.

10. The polymer compound according to claim 1, wherein the anionic polymer compound A has repeating units bonded together through at least one bond selected from an ester bond, an amide bond, an ether bond, and a urethane bond, and the anionic polymer compound B has repeating units bonded together through at least one bond selected from an ester bond, an amide bond, an ether bond, and a urethane bond.

11. 2. The polymer compound according to claim 1, wherein the value obtained by dividing the number average molecular weight of the anionic polymer compound B by the average number of monovalent anionic groups in one molecule is 100 to 5,000.

12. The content of the divalent or higher metal cation is 1 to 300 eq / 10 5 2. The polymer compound according to claim 1, wherein

13. 2. The polymer compound according to claim 1, wherein the divalent or higher metal cation is a calcium ion, a magnesium ion or an aluminum ion.

14. A marine biodegradation promoter comprising the marine biodegradable polymer compound according to any one of claims 1 to 13.

15. A marine biodegradable resin composition comprising the marine biodegradation promoter according to claim 14 and a resin.

16. The marine biodegradable resin composition according to claim 15, wherein the resin is a biodegradable resin.

17. The marine biodegradable resin composition according to claim 15, wherein the content of the marine biodegradation promoter is 1 to 50 mass% and the content of the resin is 50 to 99 mass%.

18. A molded article obtained from the marine biodegradable resin composition according to claim 15.

19. A method for producing a marine biodegradable polymer compound, comprising a step of crosslinking an anionic polymer compound A having a linear or branched main chain, a total of two or more monovalent anionic groups at the ends of the main chain, and no ionic groups in its side chain, and an anionic polymer compound B having monovalent anionic groups in the side chains of at least two repeating units, with a divalent or higher metal cation.